PATIENTS SATISFACTION ABOUT HEALTH CARE DELIVERY IN OUT-PATIENTS DEPARTMENT OF COMBINED MILITARY HOSPITAL RAWALPINDI - Tahir Sardar (Army Medical College Rawalpindi, 2020)
Objective: To determine patient’s level of satisfaction and factors leading to dissatisfaction in selected patients group with health care delivery in outpatients department of CMH Rawalpindi.